Legitimasi Esports dalam Kecabangan Olahraga: Studi Literature Review - Dhedhy Yuliawan; Ruruh Andayani Bekti (Jurnal Literasi Olahraga, 2021)
The debate about esports being included in the sports category is still ongoing even though there are studies that have stated that esports is a sport. This is the basis for this article to be written using the literature review method. This method was taken because there is still an assumption that esports is a game-playing activity that only aims to make a profit. The articles are used as a basis that the definition of esports is not only limited to playing games and making profits. In addition, the perception of esports is only limited to playing video games, even though the essence of esports is more than that. It is undeniable that esports is closely related to the economy, but through this article, the study of esports is not only seen from one side but also other characteristics that can make esports accepted as a sport. The conclusion of this article is that esports can be categorized into sports by applying the values ​​and characteristics of the sport. Such as being competitive, having rules, carried out with physical activity, training according to the program from the coach, paying attention to the nutrition of players, as well as the professionalism of players in carrying out the game